Distinct driven steady states emerge from diverse initial textures in rolled nanocomposites. (15th January 2020) - Chesser, Ian; Holm, Elizabeth A.; Demkowicz, Michael J.
Abstract: Severe plastic deformation is a widespread method of making high-performance metallic materials. Single-phase polycrystalline metals undergoing severe plastic deformation develop steady-state textures that are characteristic of the mode of deformation. By contrast, we show that two-phase, Cu-Nb nano-laminate composites reach a variety of different steady-state textures under a single mode of deformation. Using molecular statics simulations and a novel algorithm for crystal rotation analysis, we observe that the final, steady state texture and interface character in these materials depends on the initial texture of the composite. This finding suggests that the range of bulk Cu-Nb nano-composite textures that may be made by severe plastic deformation is larger than previously demonstrated, with multiple plastically-driven steady states accessible, depending on initial texture. We propose a modification of accumulative roll bonding with highly textured seed layers as a means of accessing different driven steady states in layered composites. Graphical abstract: Image, graphical abstract